Respuesta :
Answer:
6x + 4y = -16
-12x + y = -4
ok so we have to make the numbers the same so lets multiple equation 2 by 4
6x + 4y = -16
-48x+4y=-16
so then we just need to subtract
6x-(-48x)=54x
4y-4y=0
-16-(-16)=0
54x=0
0/54=0
x=0
then we just need to plug in
-12x+y=-4
so since x is 0 we can just get rid of it
y=-4
the solution is (0,-4)
now lets just check by pluging into the first equation
-6x+4y=-16
-6(0)+4(-4)=-16
0+-16=-16
-16=-16
(0,-4)
Hope This Helps!!!
Answer:
(0,-4)
Step-by-step explanation:
[tex]\tt -6x + 4y = -16 \:\:\:\boxed{ 1}\\-12x + y = -4 \:\:\:\: \boxed{ 2}[/tex]
[tex]\tt -6x + 4y = -16 \:\times2\\-12x + y = -4\: \times 1[/tex]
[tex]\tt -12x+8y=-32\\\underline{-12x+y=-4~~~~~~~}\\~~~~~~~~~~~~7y=-28\\~~~~~~~~~~~~y=-4[/tex]
Now, put y in (1)
[tex]\tt -6+4(-4)=-16[/tex]
[tex]\tt -6x=-16+16[/tex]
[tex]\tt x=0[/tex]
Hope it helps! :)